Arterial acid-base status during digestion and following vascular infusion of NaHCO3 and HCl in the South American rattlesnake, Crotalus durissus - Arvedsen, S. K.; Andersen, J. B.; Zaar, M.; Andrade, D.; Abe, Augusto Shinya [UNESP]; Wang, T. (Elsevier B.V., 2005)
Digestion is associated with gastric secretion that leads to an alkalinisation of the blood, termed the alkaline tide. Numerous studies on different reptiles and amphibians show that while plasma bicarbonate concentration ([HCO3-](pl)) increases substantially during digestion, arterial pH (pHa) remains virtually unchanged, due to a concurrent rise in arterial PCO2 (PaCO2) caused by a relative hypoventilation. This has led to the suggestion that postprandial amphibians and reptiles regulate pHa rather than PaCO2.Here we characterize blood gases in the South American rattlesnake (Crotalus durissus) during digestion and following systemic infusions of NaHCO3 and HCl in fasting animals to induce a metabolic alkalosis or acidosis in fasting animals. The magnitude of these acid-base disturbances were similar in magnitude to that mediated by digestion and exercise. Plasma [HCOT] increased from 18.4+/-1.5 to 23.7+/-1.0 mmol L-1 during digestion and was accompanied by a respiratory compensation where PaCO2 increased from 13.0+/-0.7 to 19.1+/-1.4 mm Hg at 24 h. As a result, pHa decreased slightly, but were significantly below fasting levels 36 h into digestion. Infusion of NaHCO3 (7 mmol kg(-1)) resulted in a 10 mmol L-1 increase in plasma [HCO3-] within 1 h and was accompanied by a rapid elevation of pHa (from 7.58+/-0.01 to 7.78+/-0.02). PaCO2, however, did not change following HCO3- infusion, which indicates a lack of respiratory compensation. Following infusion of HCl (4 mmol kg(-1)), plasma pHa decreased by 0.07 units and [HCO3-](pl) was reduced by 4.6 mmol L-1 within the first 3 h. PaCO2, however, was not affected and there was no evidence for respiratory compensation.Our data show that digesting rattlesnakes exhibit respiratory compensations to the alkaline tide, whereas artificially induced metabolic acid-base disturbances of same magnitude remain uncompensated. It seems difficult to envision that the central and peripheral chemoreceptors would experience different stimuli during these conditions. One explanation for the different ventilatory responses could be that digestion induces a more relaxed state with low responsiveness to ventilatory stimuli. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: arterial acid-base status; vascular infusion; Crotalus durissus